Framework for a Circumpolar Arctic Seabird Monitoring Network - Petersen, Aevar; Irons, David; Anker-Nilsen, Tycho; Artukhin, Yuri; Barrett, Robert; Boertmann, David; Egevang, Carsten; Gavrilo, Maria V.; Gilchrist, Grant; Martti, Hario; Mallory, Mark; Mosbech, Anders; et al. (Conservation of Arctic Flora and Fauna (CAFF), 2008)
List of Contributors Aevar Petersen, Icelandic Institute of Natural History, Hlemmur 3, P.O. Box 5320, 125 Reykjavik, Iceland. aevar@ni.is Anders Mosbech, Dept. of Arctic Environment, National Environ. Research Institute, Frederiksborgvej 399, Box 358, DK-4000 Roskilde, Denmark. amo@ dmu.dk Bergur Olsen, Faroese Fisheries Laboratory, Nóatún, FO-100 Tórshavn, Faroes. berguro@frs.fo Carsten Egevang, Greenland Institute of Natural Resources, P.O. Box 570, 3900 Nuuk, Greenland, E.gevang@natur.gl David Boertmann, Dept. of Arctic Environment, National Environ. Research Institute, Frederiksborgvej 399, Box 358, DK-4000 Roskilde, Denmark. dmb@ dmu.dk David Irons, U.S. Fish and Wildlife Service, 1011 E. Tudor Rd., Anchorage, Alaska AK99503, USA. david. irons@fws.gov Grant Gilchrist, Science and Technology Branch, Environment Canada, N.W.R.C., 1125 Colonel By Drive, Raven Rd., Carleton Univ., Ottawa, Ont. K1A 0H3, Canada. grant.gilchrist@ec.gc.ca Greg Robertson, Science and Technology Branch, Environment Canada, 6 Bruce Str., Mount Pearl, Newfoundland A1N 4T3, Canada. greg.robertson@ ec.gc.cad Hallvard Strøm, Norwegian Polar Institute, Polar Environmental Centre, N-9296 Tromsø, Norway. hallvardþstrom@npolar.no Henrik Osterblom, Museum of Natural History, Dept. Systems Ecol., Box 50007, SE-10691, Sweden. henroste@nrm.se Maria V. Gavrilo, Dept Polar Geography, AARI, 38 Bering St., Saint-Petersburg, 199397 Russia. mþgravrilo@mail.ru Martti Hario, Finnish Game and Fisheries Research Institute, P.O. Box 2, FIN-00791 Helsinki, Finland. martti.hario@rktl.fi Mark Mallory, Canadian Wildlife Service, Environment Canada, Box 1714, Qimugjuk Bldg 969, Iqaluit, Nunavut X0A 0H0, Canada. mark.mallory@ec.ga.ca Robert Barrett, Tromso Museum, Zoology Dept, University of Tromso, N-9037 Tromso, Norway. robb@tmu.uit.no Tycho Anker-Nilssen, NINA-NIKU, Tungasletta 2, N-7485, Trondheim, Norway. tycho@nina.no Yuri Artukhin, Kamchatka Br. Pacific Inst. of Geography, Rybakov pr., 19-a, Petropavlovsk-Kamchatsky, 683024, Russia. ...